Anticipating Regret: Why Fewer Options May Be Better - Sarver, Todd (Econometrica, 2008)
We study preferences over menus which can be represented as if the agent selects an alternative from a menu and experiences regret if her choice is ex post inferior. Since regret arises from comparisons between the alternative selected and the other available alternatives, our axioms reflect the agent's desire to limit her options. We prove that our representation is essentially unique. We also introduce two measures of comparative regret attitudes and relate them to our representation. Finally, we explore the formal connection between the present work and the literature on temptation.